Comprehensive Transcriptome Profiling Reveals Long Noncoding RNA Expression and Alternative Splicing Regulation during Fruit Development and Ripening in Kiwifruit (Actinidia chinensis) - Tang, Wei; Zheng, Yi; Dong, Jing; Yu, Jia; Yue, Junyang; Liu, Fangfang; Guo, Xiuhong; Huang, Shengxiong; Wisniewski, Michael; Sun, Jiaqi; Niu, Xiangli; Ding, Jian; et al. (Frontiers in Plant Science, 2016)
Genomic and transcriptomic data on kiwifruit (Actinidia chinensis) in public databases are very limited despite its nutritional and economic value. Previously, we have constructed and sequenced nine fruit RNA-Seq libraries of A. chinensis ‘Hongyang’ at immature, mature, and postharvest ripening stages of fruit development, and generated over 66.2 million paired-end and 24.4 million single-end reads. From this dataset, here we have identified 7,051 long noncoding RNAs (lncRNAs), 29,327 alternative splicing (AS) events and 2,980 novel protein-coding genes that were not annotated in the draft genome of ‘Hongyang’. AS events were demonstrated in genes involved in the synthesis of nutritional metabolites in fruit, such as ascorbic acids, carotenoids, anthocyanins and chlorophylls, and also in genes in the ethylene signaling pathway, which plays an indispensable role in fruit ripening. Additionally, transcriptome profiles and the contents of sugars, organic and main amino acids were compared between immature, mature, and postharvest ripening stages in kiwifruits. A total of 5,931 differentially expressed genes were identified, including those associated with the metabolism of sugar, organic acid and main amino acids. The data generated in this study provide a foundation for further studies of fruit development and ripening in kiwifruit, and identify candidate genes and regulatory elements that could serve as targets for improving important agronomic traits through marker assisted breeding and biotechnology.